Money illusion under tourists: deceived by larger numbers?. Issue 5 (4th March 2022) - Saayman, Andrea; Li, ShiNa; Fourie, Alicia; Scholtz, Marco
ABSTRACT: The difference of price perception between using foreign and home currencies is considered a form of money illusion. People may view a product as expensive in a foreign currency with a higher nominal face value, causing under-spending. Since most developing countries have considerably weaker currencies than developed countries – often the main origin of tourists – this problem have real implications for these destinations. This research investigates money illusion of tourists whose home currencies are equal to a multiple of the destination country. Framing and anchoring effects are applied to explain this form of money illusion. The results show that more than 80% of respondents suffer from money illusion. The results also demonstrate that money illusion is greater for less valuable goods, dependent on the origin of the respondent, and less prevalent under females and those with higher levels of education. Relevant implications are proposed regarding forming pricing strategy.